The Effect of Regular Exercise and Yoga on Health-Related Quality of Life Among Ovarian Cancer Survivors - Kimberly A. Lowe PhD; M. Robyn Andersen PhD; Erin Sweet ND; Leanna Standish PhD, ND; Charles W. Drescher MD; Barbara A. Goff MD (SAGE Publishing, 2012)
There is growing interest in understanding the influence of yoga on health outcomes and health-related quality of life among cancer survivors. This cross-sectional study evaluated the effects of participating in regular exercise alone or in conjunction with yoga on health-related quality of life among 219 ovarian cancer survivors using the SF-36 health survey. Multivariate regression was used to assess the association between the exercise/yoga categories on the 8 SF-36 scales. The results suggest that survivors who participated in both regular exercise and yoga had higher scores in physical functioning, fewer limitations with physical and emotional health, less pain, and more vitality than survivors who reported participating in regular exercise only. These results highlight the utility of exercise as a potential predictor of health-related quality of life in ovarian cancer survivors and support adding yoga to an exercise program.